Garcinia cylindrocarpa sp. nov. and Garcinia morotaiensis sp. nov. (Clusiaceae), new species from Indonesia - Sari, Rismita; Crayn, Darren M.; Dillon, Natalie L.; Gadek, Paul A.; Abell, Sandra (Phytotaxa, 2026)
Garcinia cylindrocarpa Kosterm. ex Sari & Crayn and G. morotaiensis Sari & N.L.Dillon are described and illustrated. Garcinia cylindrocarpa is a small tree known only from Maluku Island, North Maluku, Indonesia. It was recognised as distinct by A.J.G.H. Kostermans, who annotated specimens with the name ‘Garcinia cylindrocarpa’ and deposited them in the Type Specimen Collection of Herbarium Bogoriense (BO) but did not publish the name. Garcinia morotaiensis is a small shrub with very distinct sessile leaves known only from Morotai Island, North Maluku, Indonesia. The two species are represented in the living collections of Purwodadi Botanic Garden-BRIN, East Java, Indonesia. Molecular analysis using the internal transcribed spacer of nuclear DNA (ITS) indicates that both taxa nest within the Garcinia mangostana clade.